2006
DOI: 10.1177/152692480601600111
|View full text |Cite
|
Sign up to set email alerts
|

Family Experiences of Tissue Donation in Australia

Abstract: Seventy-seven of 140 mailed questionnaires were returned. Almost all respondents expressed satisfaction with the approach to donate, and this did not differ with the mode of approach, that is, by phone or in person. The most common reason for agreeing to donation was that it was known to be the donor's wish. The majority of respondents felt they had sufficient time and information to decide to donate, and almost all were happy with their decision and thought they had received adequate support during and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For family decision makers to make an informed choice, especially about tissue donation, which remains less familiar to the public than organ donation (Rodrigue et al 2003; Wilson et al 2006), decision makers must have a firm understanding of the processes, risks, and benefits associated with donation. These results indicate that increased efforts are needed to ensure surrogate decision makers have the requisite information that DHHS and others have deemed necessary to making informed decisions about donation.…”
Section: Discussionmentioning
confidence: 99%
“…For family decision makers to make an informed choice, especially about tissue donation, which remains less familiar to the public than organ donation (Rodrigue et al 2003; Wilson et al 2006), decision makers must have a firm understanding of the processes, risks, and benefits associated with donation. These results indicate that increased efforts are needed to ensure surrogate decision makers have the requisite information that DHHS and others have deemed necessary to making informed decisions about donation.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Empirical studies have examined attitudes and opinions toward biospecimen donation using different populations, including research participants, 19,30 general populations, 31 blood donors, 32 and family members. 33 There has been less work on the impact of the consent process on participants. A study of the meaning of consent for healthy participants in biobanks found that it was valued because it provided a sense of control and reinforced self-identity; however, the impact on participants with serious illness raises very different issues.…”
Section: Consent For Biospecimen Donationmentioning
confidence: 99%